Endemic goitre in the Sudan despite long-standing programmes for the control of iodine deficiency disorders - Abdel Monim MH Medani; Abdelsalam A Elnour; Amal M Saeed
OBJECTIVE: To describe the status of iodine deficiency disorders (IDDs) in the Sudan more than 25 years after the initiation of IDD control programmes and to explore the causes of endemic goitre in the country. METHODS: Testing for IDDs was carried out in 6083 schoolchildren 6 to 12 years of age from the capital cities of nine states in different areas of the country using the three indicators recommended by the World Health Organization: the prevalence of goitre, laboratory measurements of urinary iodine concentration in casual urine samples and serum thyroglobulin (Tg) levels. Serum levels of thyroxine (T4), triiodothyronine (T3) and thyroid-stimulating hormone (TSH), as well as urinary secretion of thiocyanate, which can affect the transport of iodine into thyrocytes, were also measured. FINDINGS: The prevalence of goitre in the different samples ranged from 12.2% to 77.7% and was 38.8% overall. The overall median urinary iodine concentration was 6.55 µg/dl, with the lowest median value having been found in Kosti city (2.7 µg/dl), situated in the centre of the country, and the highest (46.4 µg/dl) in Port Sudan, on the Red Sea coast. The highest mean serum Tg level (66.98 ng/ml) was found in Kosti city, which also had the highest prevalence of goitre. CONCLUSION: IDDs still constitute a public health problem throughout urban areas in the Sudan and iodine deficiency appears to be the main etiological factor involved.